Urgensi Kebijakan Kenaikan Tarif Cukai Rokok Elektrik di Indonesia - Siti Sarah Solihat; Gunadi (Owner : Riset dan Jurnal Akuntansi, 2023)
The Indonesian Government added electric cigarettes (e-cigarettes) as excise objects to improve the cigarette excise policy. Since 2018, the level of e-cigarettes has increased continuously. The age distribution of smokers who consume e-cigarettes is also starting to be troubling. Tobacco Control Support and the Association of Indonesian Public Health discovered that many e-cigarettes smoker are young children and teenagers. To reduce the prevalence rate of smokers, especially among children and teenagers, the Indonesian government made a policy to increase the excise tariffs and its minimum retail selling price. Increasing cigarette excise is often a problem because it has many impacts on other related sectors. In contrast to regular cigarettes, e-cigarettes had not much relation to many other sectors so the researchers aim to see whether increases in e-cigarette excise and minimum retail prices can help the government achieve its goals. By the government making an excise tariff policy, several sectors must be considered such as state revenue, consumption levels, involved sectors, and controlling illegal cigarettes. The tariff system and excise structure are also important instruments for the government to control the level of cigarette consumption. Researchers used qualitative methods and descriptive techniques to analyze data. The increase in excise tariffs for e-cigarettes has not reached its maximum, however increasing retail prices of e-cigarettes could also reduce consumption levels, especially the prevalence of using e-cigarettes among young kids and teenagers.